(untitled) (Construction Economics and Building, 2026)
This conceptual paper introduces the responsive scaffold model (RSM), a theoretically grounded pedagogical and assessment framework designed to enhance soft skills development in construction management education. Using theoretical synthesis methodology, RSM integrates scaffolding theory, cognitive apprenticeship, and experiential learning into a cohesive framework. The model’s theoretical foundations are well-established in educational literature, with each component drawing upon substantial research evidence from related contexts. Although developed within Australian higher education, the paper illustrates RSM’s broader applicability across disciplines and international contexts. The model’s responsiveness ensures tailored support that adapts to learners’ evolving abilities, systematically reducing cognitive overload whilst maintaining academic rigour. Comparisons with problem-based and simulation-based learning highlight RSM’s distinctive approach to balancing structured guidance and learner autonomy. Implementation guidelines cover curriculum design, faculty development, and authentic assessment, demonstrating RSM’s scalability in large classes and digital settings. By aligning with educational standards and industry expectations, RSM offers a sustainable, learner-centred approach that bridges theoretical knowledge and real-world practice, advancing construction management education to enhance graduate employability and professional readiness. Future research directions are outlined to guide empirical validation of this conceptual framework.